2017
DOI: 10.1108/jedt-06-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of innovation orientations in construction companies

Abstract: Purpose An organisation’s performance tends to be associated with its innovativeness. However, innovation remains challenging in the construction industry, partially due to the complex nature of this industry. Nevertheless, innovation orientations (i.e. creation and adoption) shed new light on innovation in the construction industry. These orientations are similar but not entirely identical. Although most studies do not discuss these orientations in any detail, this study aims to classify the characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 86 publications
1
26
0
Order By: Relevance
“…Nevertheless, a high level of innovation performance is extremely important for the industry's growth and the development a country economy. Many studies have been undertaken to examine innovationrelated topics in the field of construction management (Egbu 2004;Stewart 2007;Panuwatwanich et al 2008Panuwatwanich et al , 2009aPanuwatwanich et al , 2009bDavidson 2013;Ozorhon 2013;Davis et al 2016;Dansoh et al 2017;Yusof et al 2017). It is worth noting, that most of the aforementioned studies have addressed innovation processes in the industry by mainly focusing at the project and firm level.…”
Section: Construction Innovation Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a high level of innovation performance is extremely important for the industry's growth and the development a country economy. Many studies have been undertaken to examine innovationrelated topics in the field of construction management (Egbu 2004;Stewart 2007;Panuwatwanich et al 2008Panuwatwanich et al , 2009aPanuwatwanich et al , 2009bDavidson 2013;Ozorhon 2013;Davis et al 2016;Dansoh et al 2017;Yusof et al 2017). It is worth noting, that most of the aforementioned studies have addressed innovation processes in the industry by mainly focusing at the project and firm level.…”
Section: Construction Innovation Processesmentioning
confidence: 99%
“…Based on the existing construction management literature (Seaden and Manseau 2001;Panuwatwanich et al 2009a;Van Egmond 2012;Xue et al 2014;Orstavik et al 2015;Yusof et al 2017) and previously conducted studies (Suprun and Stewart 2015;Suprun et al 2016), we have identified three main factors that influence or force decision-makers within construction companies to acknowledge innovation implementation as a priority to improve efficiency and effectiveness:…”
Section: Measurement Of Innovation Performancementioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing literature on the adoption and implementation of BIM and the established literature on innovation by developing the notion of contexts integrated in the innovation process. The performance of an organization tends to be associated with its capacity for innovation, being it a challenge in the construction industry, partly due to the complex nature of this industry (Yusof et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As with the adoption of any innovation or new technology, previous studies have established that construction firms face a host of difficulties due to limitations such as the unique social, economic and technological contexts of developing countries (Bui et al, 2016). Adoption of new technology or processes remains challenging in the construction industry (Nor'Aini Yusof, 2017), which is known to be lagging behind in adopting new ideas, technologies and processes. Therefore, it would not be surprising if BIM technology received a slow response from the industry players (Rogers et al, 2015, Liao et al, 2017.…”
Section: Introductionmentioning
confidence: 99%